The Integration of Contemporary Islamic Education into International and Global Education: A Comparative Study - Ferdino, Muhammad Farhan; Mortalisa, Tara Putri; Oviyanti, Fitri; Maryamah, Maryamah (FKIP - Universitas Riau, 2025)
Islamic education has diverse forms and systems, adapted to the culture, regulations, and educational policies of each country, including Indonesia. This study aims to analyze the comparison between Islamic education from the perspective of international and global education in the contemporary era. This study employs a qualitative approach using a library research method, which reviews literature from various scholarly sources related to Islamic education, educational internationalization, and globalization. The findings indicate that international education focuses on strengthening cross-country collaboration through student exchange, academic cooperation, and the implementation of international curricula. Meanwhile, global education emphasizes the development of multicultural awareness and the reinforcement of identity as global citizens by integrating global values into the education system. Both have a significant impact on the development of modern Islamic education that is responsive to changes over time. These findings highlight the importance of integrating local and Islamic values with the principles of international and global education to create an Islamic education system that is adaptive, competitive, and contextually relevant in addressing global challenges.